THE INFLUENCE OF BRAND IMAGE, AND SERVICE QUALITY TOWARD CONSUMER PURCHASE INTENTION OF BLUE BIRD TAXI MANADO - Mambu, Evans (FEB Universitas Sam Ratulangi Manado, 2015)
A company must do more than make good services, they have to inform consumers about the quality of service and carefully position their service quality in consumersâ€™ mind. Recently the marketer weapons that include brand image and service quality are proved as effective moves by top companies to deliver their purpose as a main preference to all consumers. The purpose of this study was to find out whether there is significance influence between brand image, and service quality toward consumer purchase intention of Blue Bird Taxi Manado. The method of this research is purposive analysis and the data is obtained from questionnaire that distributed to the user of Blue Bird Taxi in Manado. The analysis methods are multiple regression analysis, statistical f test, statistical t test and test of the classical assumption. The sample of this research is 100 from user of Blue Bird Taxi in Manado. Based on the research that has been conducted, the result showed that Brand Image and Service Quality have a positive influence on consumer purchase intention. However, Service quality is showed not significantly on consumer purchase intention. The company should improve the quality of service as their marketing tools. Â Keywords: brand image, service quality, consumer purchase intention